Genetic diversity studies in soybean (Glycine max L. Merrill) germplasm: Genetic diversity studies in soybean (Glycine max L. Merrill) germplasm - S S NICHAL; P V PATIL; M S DANDGE; G D CHANDANKAR (Journal of Oilseeds Research, 2023)
Hundred soybean genotypes along with five checks were evaluated to study the nature and magnitude of genetic divergence using Mahalanobis’s D2 Statistics. The data was recorded on nine important quantitative traits from the genotypes grown in Augmented Block Design. The characters plant height, number of pods/plant, days to 50% flowering, days to maturity and 100 seed weight contributed maximum towards genetic diversity. The genotypes grouped into 6 clusters, cluster I was larger containing 60 genotypes whereas cluster V has smallest cluster containing only one genotype. On the basis of clusters formed genotypes were selected to be utilized as donor like NRC 105, JS 20-34 and JS 95-60 for earliness; Kalitur and AGS 25 for more number of pods and branches; Karune for bold seed and AMS 100-39 and AMS 48-7-3 for high seed yield. On the basis of average inter cluster distance the cross AMS 48-7-3 x Kalitur and AMS 100-39 x AMS 48-7-3 were suggested for getting more number of pods and branches with high yield. The cross combination Karune x Kalitur, AMS 48-7-3 x Karune and AMS 100-39 x Karune were suggested for getting extra bold seeded high yielding variety.